Desenvolvimento de método para quantificação de metais e metalóides em amostras de fígado bovino in natura por espectrometria de fluorescência de raios-x por reflexão total - Liliani Pacheco Tavares Nazareth (2023)
In this work, a method was developed for the quantification of metals and metalloids Al, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Rb, Sr, Nb, Cd, Ba, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Hg, Pb, Th and U in in natura bovine liver by total reflection X-ray fluorescence spectrometry (TXRF). Multielement analyzes make it possible to evaluate essential and toxic elements, as well as possible chemical tracers, which can establish a relationship between probable intoxication and the origin of environmental contaminants. The method consisted of grinding the bovine liver in natura with an HNO3 solution in a ball crusher/mill. The influence of the variables HNO3 concentration, acid volume and milling time were evaluated using a 23-1 fractional factorial design, with the best optimization condition found in a HNO3 concentration of 10% v v-1 and a volume of 6 mL, with a stirring time of 12 minutes for further analysis of the metals contained in the suspension. Method validation was performed according to the parameters recommended by MAPA, including limits of detection (LD) and quantification (LQ), repeatability, intermediate precision, accuracy and robustness. The certified reference materials used were standard solutions in addition to MRC NIST 1577c Bovine Liver. The accuracy of the method was evaluated using the fortified white matrix, and the coefficients of variation obtained in the repeatability and intermediate precision steps ranged from 2.22 to 18.7% and from 3.02 to 18.1%, respectively. The accuracy of the method was evaluated using the recovery percentage results obtained in the repeatability and intermediate precision steps, and by studying the recovery with NIST 1577c, ranging from 79 to 119% for most of the investigated analytes. The limits of quantification of the method (LQM) obtained are adequate for the purpose of the method, being 0.11 mg kg-1 for As and 0.15 mg kg-¹ for Pb. Regarding robustness, the method proved to be robust, as the results of the analyzes were little affected by varying the evaluated factors. For application of the method, samples of bovine liver acquired in the commercial network, four from the interior of Minas Gerais and one from the capital, were analyzed and compared to the maximum limits allowed by the Collegiate Board of the National Health Surveillance Agency (ANVISA), with the maximum tolerated limits (LMT) for bovine liver being 0.50 mg kg-¹ for Pb and 1.0 mg kg-¹ for As. The results showed that the bovine liver samples studied did not present levels above those allowed for these metals and the developed analytical method presented simplicity and good performance, being able to be used in the bovine liver analysis.